The Role of Brand Awareness in Mediating the Relationship Between Content Marketing and Electronic Word of Mouth (E-WOM) on Purchase Intention of Tenue de Attire Products - Alkhila Habibatul Jannah; Wilma Cordelia Izaak (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The development of social media, especially TikTok, has become a strategic opportunity for fashion brands to expand their marketing reach, including Tenue de Attire. However, despite appearing frequently on the For You Page (FYP), there are still many users who do not realize that Tenue de Attire is a brand that sells fashion products and when compared to other local products, Tenue De Attire has the lowest number of products sold. Through brand awareness, this research seeks to examine how electronic word-of-mouth (e-wom) and content marketing affect purchase intention. Gen Z Surabaya TikTok users made up the study's population. With a sample size of 126 respondents, this study employed the purposive sampling method. The findings of this study show that while electronic word-of-mouth (e-WOM) exerts a positive and significant influence on brand awareness, content marketing does not demonstrate a noticeable effect. Furthermore, purchase intention is positively and significantly affected by brand awareness. In addition, e-WOM shows a positive and substantial indirect impact on purchase intention mediated by brand awareness, whereas content marketing appears to have no indirect influence in this regard.